A qualitative investigation into the levers and barriers to weight loss in children: opinions of obese children. Issue 11 (4th July 2006) - Murtagh, J; Dixey, R; Rudolf, M
Abstract : Background: The alarming increase in the worldwide prevalence of childhood obesity is now recognised as a major public health concern. Failure to isolate and understand the external and internal factors contributing to successful weight loss may well be contributing to the ineffectiveness of current treatment interventions. Aim: To identify the physical and psychological levers and barriers to weight loss experienced by obese children using qualitative techniques. Methods: 20 participants were randomly selected from a population of clinically obese children (7–15 years old) attending a weight-loss clinic for >3 months. The children expressed their opinions in a series of interviews and focus group sessions. Data were recorded, semitranscribed and analysed using the thematic framework analysis technique and behavioural-change models. Results: Children described the humiliation of social torment and exclusion as the main reasons for wanting to lose weight, although initiation of behavioural change required the active intervention of a role model. The continuation of action was deemed improbable without continual emotional support offered at an individual level. Behavioural sacrifice, delayed parental recognition and previous negative experiences of weight loss were recognised as barriers to action. Participants identified shortcomings in their own physical abilities, the extended time period required to lose weight and external restrictions beyond their control as barriers to maintaining behavioural change. Discussion: This study identifies the important levers and barriers experienced by obese children in their attempt to lose weight. Dealing with these levers and barriers while acknowledging the complex interplay of social and emotional factors unique to the individual may well promote successful weight control.